Taxonomic observations on stingrays of the genus Dasyatis (Chondrichthyes: Dasyatidae) in the Gulf of Gabès (Southeastern Mediterranean Sea) - Saadaoui, Abdesselem; Saidi, Bechir; Elglid, Aziza; Séret, Bernard; Bradai, Mohamed N. (Zootaxa, 2016)
Four species of stingrays of the genus Dasyatis occur in the Gulf of Gabès, but the taxonomic status of one of them, D. tortonesei has been questioned by several authors, and synonymized with D. pastinaca by some. The present study, using morphological comparisons and genetic analyses, demonstrates that there is a closely related species to D. pastinaca in the Gulf of Gabès, but distinguishable by several characters. This species is provisionally identified as Dasyatis cf. tortonesei, pending a more extensive comparative study including specimens from other regions of the Mediterranean Sea and eastern North Atlantic Ocean.